EFEKTIVITAS PENGAWASAN CLOSED CIRCUIT TELEVISION (CCTV) DALAM MENINGKATKAN PERILAKU KEDISIPLINAN SISWA PADA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM KELAS XII DI SMK N 3 WONOSARI - Purnomo, Aji (Al Ghazali, 2018)
The background of the problem in this research is that there is still an indiscipline of students towards school regulations, especially in Islamic Education learning. The indiscipline raises the Muraqabatullah concept that is applied by schools in helping to improve student discipline, namely through Closed Circuit Television (CCTV) in the classroom. This research is a qualitative research by taking place at SMK Negeri 3 Wonosari. Data collection is done by conducting observations, in-depth interviews, and documentation. The validity test of the data used is triangulation with the source. The results of this study indicate that (1) Discipline learning of class XII students at Vocational High School 3 Wonosari takes place quite well, and school regulations run quite well in disciplining students. (2) The effectiveness of CCTV in improving student discipline in Islamic Education learning is considered quite effective. Student‟s discipline is not only due to CCTV factors. (3) The main problem in using CCTV in the classroom is that there is no special attention in supervision. Solution from school; convey to the teacher concerned at a certain time that there are students who are not disciplined in class, additional CCTV monitoring, and periodic maintenance.